Interpersonal Support And Motivation Of Woman Of Childbearing Age In VIA Examination: A Cross-Sectional Study - Hani Muhayah; Happy Dwi Aprilina; Yektiningtyastuti yektiningtyastuti; Reni Purwo Aniarti (Media Keperawatan Indonesia, 2026)
Cervical cancer is one of the leading causes of death among women in Indonesia. The VIA examination is important for early detection, but the participation of women of childbearing age is still low, partly due to the lack of interpersonal support from husbands, family, health workers, and friends. To determine the relationship between interpersonal support (husband, family, health workers, and friends) and motivation of WUS members of PCA Aisyiyah Gumelar to undergo VIA examination. This quantitative research uses a correlation study design with a cross-sectional approach. A sample of 82 women of childbearing age (WUS) was taken using total sampling techniques. Data was collected through an interpersonal support questionnaire including husband, family, health workers, friends, and motivation, with a research time frame of May 31, 2025, and analyzed using the Spearman rank test (α = 0.05) and logistic regression. The results show a significant relationship between interpersonal support and the motivation of WUS. Support from husbands (p = 0.000; r = 0.533), support from family (p = 0.000; r = 0.614), support from health workers (p = 0.000; r = 0.485), and support from friends (p = 0.000; r = 0.491). Interpersonal support from husbands, family members, healthcare workers, and peers is significantly associated with motivation to undergo VIA screening. These findings indicate statistical associations rather than causal relationships.